Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization - Tawade, Bhausaheb V.; Salunke, Jagadish K.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2014)
A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50: 50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co) polyesters exhibited inherent viscosities in the range 0.70-1.21 dL g(-1) and number-average molecular weights in the range 16,000-48,200 (GPC, polystyrene standard). Polyesters were soluble in common organic solvents such as chloroform and dichloromethane and could be cast into films from chloroform solution. Polyesters exhibited T-10 values in the range 430-455 degrees C and Tg values were in the range 29-202 degrees C. Dynamic mechanical storage modulus and maximum on transition of tan delta curve decreased with increased content of HPPDP in copolyesters. Importantly, the large difference between Tg and T-10 values offers the possibility to process these polyesters in the melt.
Keywords: Aromatic polyesters; Cashew nut shell liquid; pentadecyl; Polycondensation; processability; Thermal properties

Pyrene based conjugated materials: synthesis, characterization and electroluminescent properties - Salunke, Jagadish K.; Sonar, Prashant; Wong, F. L.; Roy, V. A. L.; Lee, C. S.; Wadgaonkar, Prakash P. (Physical Chemistry Chemical Physics, 2014)
In this work, three novel pyrene cored small conjugated molecules, namely 1,3,6,8-tetrakis(6-(octyloxy)naphthalene-2-yl) pyrene (PY-1), 1,3,6,8-tetrakis((E)-2-(6-(n-octyloxy) naphthalene-2-yl) vinyl) pyrene (PY-2) and 1,3,6,8-tetrakis((6-(n-octyloxy) naphthalene-2-yl) ethynyl) pyrene (PY-3) have been synthesized by Suzuki, heck and Sonogashira organometallic coupling reactions, respectively. The effects of single, double and triple bonds on their optical, electrochemical, and thermal properties are studied in detail. These all materials are fluorescent and they have been used in organic light-emitting diodes (OLEDs) and their electroluminescent properties have been studied.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P. (Journal of Materials Chemistry C, 2016)
Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1,3,6,8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1,3,6,8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA) and a phenothiazine substituent (PY-PH) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance. PY-CA exhibited the maximum brightness at around 2500 cd m(-2) and the power efficiency of 1.5 lm W-1 while that of PY-PH exhibited 2116 cd m(-2) and 0.45 lm W-1 respectively.

Crystallisation-enhanced bulk hole mobility in phenothiazine-based organic semiconductors - Shinde, D. B.; Salunke, Jagadish K.; Candeias, Nuno R.; Tinti, Francesca; Gazzano, Massimo; Wadgaonkar, P. P.; Priimagi, Arri; Camaioni, Nadia; Vivo, Paola (Scientific Reports, 2017)
A series of three novel donor-acceptor systems based on C(3)-malononitrile-substituted phenothiazines was synthesised in good overall yields and their thermal, spectroscopic, and electrochemical properties were characterised. The compounds were prepared through a sequence of Ullmann-coupling, Vilsmeier-Haack formylation and Knoevenagel-condensation, followed by Suzuki-coupling reactions for introduction of aryl substitutents at C(7) position of the phenothiazine. The introduction of a donor unit at the C(7) position exhibited a weak impact on the optical and electrochemical characteristics of the compounds and led to amorphous films with bulk hole mobilities in the typical range reported for phenothiazines, despite the higher charge delocalisation as attested by computational studies. In contrast, highly ordered films were formed when using the C(7)-unsubstituted 3-malononitrile phenothiazine, exhibiting an outstanding mobility of 1 x 10(-3) cm(2) V-1 s(-1), the highest reported for this class of compounds. Computational conformational analysis of the new phenothizanes suggested that free rotation of the substitutents at the C(7) position suppresses the ordering of the system, thereby hampering suitable packing of the new materials needed for high charge carrier mobility.